Rumination and Age: Some Things Get Better - Stefan Sütterlin; Muirne C. S. Paap; Stana Babic; Andrea Kübler; Claus Vögele (Journal of Aging Research)
Rumination has been defined as a mode of responding to distress that involves passively focusing one's attention on symptoms of distress without taking action. This dysfunctional response style intensifies depressed mood, impairs interpersonal problem solving, and leads to more pessimistic future perspectives and less social support. As most of these results were obtained from younger people, it remains unclear how age affects ruminative thinking. Three hundred members of the general public ranging in age from 15 to 87 years were asked about their ruminative styles using the Response Styles Questionnaire (RSQ), depression and satisfaction with life. A Mokken Scale analysis confirmed the two-factor structure of the RSQ with brooding and reflective pondering as subcomponents of rumination. Older participants (63 years and older) reported less ruminative thinking than other age groups. Life satisfaction was associated with brooding and highest for the earlier and latest life stages investigated in this study.